AGROTOURISM AS A FACTOR OF SUSTAINABLE RURAL DEVELOPMENT (Scientific journal of the Fergana State University, 2024)
The article examines new comprehensive approaches to the development of rural tourism and their impact on the sustainable development of rural areas. The main goal is to analyze the strengths and weaknesses, opportunities and threats of further development of agrotourism. Using the general indicator of the joint development of agriculture and rural tourism, the researcher proposed promising directions that help the sustainable development of rural areas in the field of agrotourism in Fergana region.